Incidence of zoonotic parasites on beaches in the capital of Alagoas (Research, Society and Development, 2022)
The presence of parasites in areas of fishing practices for eggs and larvae of geohelminths is a public health problem, since fishermen are potential hosts. This study evaluated the contamination of beaches in the municipality of Maceió, AL, by helminth larvae, in order to survey the places where there is a higher incidence of geohelminthiasis. Thirty-six samples were collected on Jatiúca and Jaraguá beaches. They had as an inclusion criterion the regular practice of fishing. Twelve collection points were selected, and in each area 18 samples of 150g were collected, being: one superficial; depth of 10 cm, and 20 cm, at alternating times in the morning, afternoon and night, totaling 36 samples that were analyzed by the method of Hoffmann and Rugai adapted for soil. One point was observed at Praia da Jatiúca, with two negative samples for any type of geohelminth. Thus, 94.44% of the samples were found eggs or larvae of intestinal parasites, observed at a depth of 10 to 20 cm (77.7%), while on the surface, 22.3% of the samples were positive. The results demonstrated the prevalence of Ancylostoma spp. and Trichuris trichuria, which can compromise human health and act as a form of infection in the environment.